1986
DOI: 10.1177/0310057x8601400106
|View full text |Cite
|
Sign up to set email alerts
|

Thiopentone Cerebral Protection under EEG Control during Carotid Endarterectomy

Abstract: Seventy patients who underwent a total of 77 consecutive carotid endarterectomies were given thiopentone (mean dose 19 mg/kg) under EEG control for cerebral protection during the period of carotid clamping. This technique was used instead of elective insertion of a temporary bypass shunt in response to adverse EEG changes occurring after clamping. The EEG was monitored continuously throughout operation. The EEG burst-suppression pattern with electrically inactive periods of 30-60 seconds was taken as indicatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…High-dose Pentothal was administered to produce burst-suppression, and operation was completed in all seven patients without neurologic deficit. Hicks et al 2 a morbidity and mortality rate of 1.5% in 200 operations.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…High-dose Pentothal was administered to produce burst-suppression, and operation was completed in all seven patients without neurologic deficit. Hicks et al 2 a morbidity and mortality rate of 1.5% in 200 operations.…”
Section: Discussionmentioning
confidence: 98%
“…9 ,10 Kassel et allO demonstrated that Pentothal, titrated against continuous electroencephalographic recording in doses sufficient to produce maximum reduction in cerebral blood flow and metabolism without cardiovascular depression, produced burst-suppression activity at 30-to 60-second intervals, the level of burst-suppression we have adopted as the monitor of Pentothal dosage. 2 In the clinical setting of carotid endarterectomy, Gross et al ll reported seven patients in whom ischemic electroencephalographic changes developed with clamping. After adjustment of anesthesia to produce hypertension, clamping again produced ischemic changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, an audit in South Australia ( n = 223 patients) showed that CEA was not associated with a decrease in the incidence of stroke and death at 12 months as anticipated 9 . Individual Australian vascular units also have reported CEA data 10–31 . In preparation for a state‐wide audit, we conducted a telephone survey of all vascular surgeons within NSW in order to determine pre‐existing CEA audit practices.…”
Section: Introductionmentioning
confidence: 99%